STRATEGI SMART BRANDING DALAM PEMBANGUNAN SMART CITY DI KABUPATEN DEMAK - EB, Gita Aprinta; Pungkasanti, Prind Triajeng; Handayani, Titis (Master of Communication Science Program, Universitas Diponegoro, 2024)
The integration of smart city concepts into urban management has become a prominent strategy for addressing global urbanization challenges. This study examines the implementation of smart branding strategies within the smart city framework of Demak Regency, Indonesia. Drawing from qualitative methods, including interviews with local authorities and focus group discussions with community stakeholders (14 people),, the research highlights the alignment of smart branding initiatives with sustainable development goals and the enhancement of local economic potential. Smart branding in Demak emphasizes leveraging cultural and historical identity, transitioning from its traditional image as a